Exploring the Educational Potential of Virtual Reality and Mixed Reality: Immersive Learning, Student Engagement, and Knowledge Retention - Dodevska, Mila; Atanaskoski, Zivko; Jovanov, Mile; Stankov, Emil; Lameski, Petre (Faculty of Computer Science and Engineering, Ss. Cyril and Methodius University, Skopje, Macedonia, 2025)
The integration of Virtual Reality (VR) and Mixed Reality (MR) technologies in education presents new opportunities for immersive and interactive learning. This paper reviews recent applications of VR/MR in educational contexts, emphasizing their impact on student engagement, cognitive development, and knowledge retention. The analysis highlights key benefits such as enhanced motivation, improved practical skills, and effective visualization of abstract content, while also acknowledging limitations including cognitive load and motion sickness. In addition to the literature review, the grounds of an experimental study are presented.
Keywords: Virtual Reality (VR), Mixed Reality (MR), Immersive Learning, Student Engagement, Knowledge Retention, E-learning, Educational Technology